Elucidating the mechanism of corneal epithelial cell repair: unraveling the impact of growth factors - Gong, Jinjin; Ding, Gang; Hao, Zhongkai; Li, Yuchun; Deng, Aijun; Zhang, Chenming (Frontiers in Medicine, 2024)
The repair mechanism for corneal epithelial cell injuries encompasses migration, proliferation, and differentiation of corneal epithelial cells, and extracellular matrix remodeling of the stromal structural integrity. Furthermore, it involves the consequential impact of corneal limbal stem cells (LSCs). In recent years, as our comprehension of the mediating mechanisms underlying corneal epithelial injury repair has advanced, it has become increasingly apparent that growth factors play a pivotal role in this intricate process. These growth factors actively contribute to the restoration of corneal epithelial injuries by orchestrating responses and facilitating specific interactions at targeted sites. This article systematically summarizes the role of growth factors in corneal epithelial cell injury repair by searching relevant literature in recent years, and explores the limitations of current literature search, providing a certain scientific basis for subsequent basic research and clinical applications.